2021
DOI: 10.3390/nu13114006
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Plasma Choline and the Betaine-to-Choline Ratio in Response to 6-Month Lifestyle Intervention Are Associated with the Changes of Lipid Profiles and Intestinal Microbiota: The ICAAN Study

Abstract: Trimethylamine N-oxide (TMAO) and its precursors, including choline, betaine, and L-carnitine, are gut microbiota-related metabolites associated with the risk of obesity. We aimed (1) to comprehensively examine whether the changes in plasma TMAO and its precursors induced by lifestyle intervention are associated with the improvements in plasma metabolic parameters; and (2) to identify the fecal microbiome profiles and nutrient intakes associated with these metabolites and metabolic index. Data from 40 particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Interestingly, a lower abundance of Romboutsia spp. has been recently associated with lower LDL-cholesterol levels and a higher intake of fibers (37). Moreover, we have assessed the fecal SCFAs and MCFAs abundances and, in line with the absence of remarkable compositional modifications in GM, no statistically significant differences were reported after the probiotic administration.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Interestingly, a lower abundance of Romboutsia spp. has been recently associated with lower LDL-cholesterol levels and a higher intake of fibers (37). Moreover, we have assessed the fecal SCFAs and MCFAs abundances and, in line with the absence of remarkable compositional modifications in GM, no statistically significant differences were reported after the probiotic administration.…”
Section: Discussionmentioning
confidence: 73%
“…Interestingly, a lower abundance of Romboutsia spp. has been recently associated with lower LDL-cholesterol levels and a higher intake of fibers ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, identifying correlations between intestinal microbiota and fecal metabolites can enhance our understanding of intestinal microbiota function and regulatory effects on human health and disease. For example, a lifestyle intervention study and screen of gut microbiota with metabolite profiling by Jang and colleagues ( 48 ) showed that choline and betaine, which contribute to the risk of obesity, could serve as reliable biomarkers of metabolic changes driven by lifestyle interventions, and that their levels were affected by diet and gut microbiota. In our study, we observed a wide range of betaine levels after fasting, particularly in the Chinese group, but found no correlation between betaine and specific taxa, although other studies reported significant correlations between betaine levels and certain potentially beneficial bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Anaerotignum faecicola and Bacteroides stercoris were associated with a decreased B/C ratio. Volunteers with both increased choline and a decreased B/C ratio had higher abundance of Romboutsia timonensis, Granulicatella adiacens , and Pediococcus stilesii ( 198 ). While it is exciting to see specific bacterial species identified as playing a role in TMAO biology, future RCTs that examine the effects of MedDiet on TMAO are required to draw conclusions on this topic.…”
Section: Interplay Of Obesity the Meddiet And Gut-derived Metabolitesmentioning
confidence: 99%